Saikosaponin A Inhibits Breast Cancer by Regulating Th1/Th2 Balance - Zhao, Xin; Liu, Jinyu; Ge, Shasha; Chen, Chen; Li, Shuang; Wu, Xiaoyu; Feng, Xuanye; Wang, Yueqi; Cai, Dayong (Frontiers in Pharmacology, 2019)
Saikosaponin a (SSa) is isolated from the dried root of Radix Bupleuri, a herb widely used in traditional Chinese medicine, exerting anti-tumor activities. The T helper cell type 1(Th1)/Th2 balance is associated with anti-tumor immunity in breast cancer. The present study aimed to investigate the effects of SSa on Th1/Th2 balance in breast cancer, and to explore the underlying mechanisms. Breast cancer in rats was induced by intragastrical administration of 7,12-dimethyl-benz[a] anthracene once (100mg/kg). At d91, the rats suffering from tumors were randomly divided into three groups, and treated with vehicle solution (control group), tamoxifen (TAM group), and SSa (SSa group) daily for 56 days, respectively. The tumor volume reduction ratio and tumor cell proliferation were detected to assess anti-tumor effect of SSa. The positive staining numbers of CD8+ and CD4+ T cells infiltrated in breast tumors were measured by immunohistochemistry to evaluate the anti-tumor immunity of SSa. Cytokine levels in serum secreted by Th1 cells (interferon gamma (INF-γ), interleukin (IL)-12) and Th2 cells (IL-4, IL-10) were detected to evaluate Th1/Th2 balance. The related molecules of IL-12/signal transducers and activators of transcription 4 (STAT4) pathway were detected by immunohistochemistry staining, RT-PCR and western blot to explore the mechanisms of SSa. The results showed that, compared with control group, SSa significantly inhibited tumor growth and tumor cell proliferation. SSa enhanced anti-tumor immunity, which was demonstrated as increased CD8+ T cells and CD4+ T cells infiltrated in tumors. SSa shifted Th1/Th2 balance towards Th1, which was confirmed as increased serum INF-γ and IL-12 levels, while decreased serum IL-4 and IL-10 levels. SSa increased IL-12, IL-12 receptor and phosphorylated STAT4 expressions to promote Th1 differentiation. In conclusion, the present work suggested that SSa could inhibit breast cancer growth by shifting Th1/Th2 balance towards Th1. The underlying mechanism may involve activation of IL-12/STAT4 pathway that induced Th1 differentiation.